2015
DOI: 10.18801/jbar.050215.55
|View full text |Cite
|
Sign up to set email alerts
|

Goat husbandry practices in Southern region of Bangladesh

Abstract: Data were collected from a total of 41 goat farmers in 26 different villages of Barguna and Patuakhali district of Bangladesh to explore knowledge about the goat husbandry practices. Most of the farmers reared goats in semi-intensive system, took winter care and took bath of their goats in the summer. Main feed item of goats were green grass, tree leaves and main water source was pond though some farmers supplied concentrate to their goats. However, most of goat farmers used vaccine against PPR disease and de-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
(7 reference statements)
3
15
0
Order By: Relevance
“…The major sources of feed ingredients they provided to goats were own sources which were mainly tree leaves, green grasses and roadside grasses. Hossain et al (2015) reported that the feed used by 61%, 19.5% and 19.5% goat farmers were green grass alone, green grass +straw, and green grass + concentrate, respectively. They also found that 65.9% and 39% goat farmers supply green grass and concentrate feed respectively to their goats when they keep goats inside the house.…”
Section: Feeds and Feeding Managementmentioning
confidence: 99%
“…The major sources of feed ingredients they provided to goats were own sources which were mainly tree leaves, green grasses and roadside grasses. Hossain et al (2015) reported that the feed used by 61%, 19.5% and 19.5% goat farmers were green grass alone, green grass +straw, and green grass + concentrate, respectively. They also found that 65.9% and 39% goat farmers supply green grass and concentrate feed respectively to their goats when they keep goats inside the house.…”
Section: Feeds and Feeding Managementmentioning
confidence: 99%
“…They also found that 65.9% of farmers supplied green grass while 39% farmers supplied concentrate feed to their goats during keeping goats inside house. Drinking water sources were (46.3%) tube well, (51.2%) pond and (2.4%) supply water (Hossain et al, 2015). They also reported during rainy season goat rearing farmers in the southern region supplied (46.3%) green tree leaves, (19.5%) green grass and (34.1%) green tree leaves and green grass to their goats but at rain time 29.3% farmers grazed their goats.…”
Section: Feeding Managementmentioning
confidence: 99%
“…Most of the farmers (82% and 56.1%) of central and southern region of Bangladesh did not take bath of their goats, only 18% and 43.5% farmers took bath of their goats during winter season. Maximum farmers (80.5%) reared goats in semi-intensive system but few farmers (7.3%) used confinement system of rearing, while 12.2% farmers used free range system in the southern region (Hossain et al, 2015). They also found that most (100%) of the goat farmers took bath of their goats in the summer season but only 4.9% farmers took bath of their goats daily in the summer season.…”
Section: Rearing Management Systemmentioning
confidence: 99%
See 2 more Smart Citations